Claim and warrant: a contextual physics learning strategy to enhance studens' argumentation skills. (June 2020) - Viyanti,; Cari,; Sunarno, W; Prasetyo, Z K; Maulina, H
Abstract: Students' argumentation skills both in the learning process and assessment to realize the transformation of the production of quality claim and warrant are very important to be implemented. This study is trying to analyze the process of students' argumentation skills transformation through a contextual physics learning strategy called "Claim and Warrant". This study used descriptive survey method with eleven grade student in Bandar Lampung as the population. Beside that, cluster random sampling technique was used to specify the sample. A complex problems as an exercise were given to thirty two senior high school students in order to produce alternative statements and the basis of theoretical-evidence relations. The data were obtained through reasoned multiple choice tests with feedback andanalyzed through a feedback-assessment process. The results showed the increasing of students' argumentation skills in form of production of alternative statements and counter.